Analisis Potensi Pariwisata di Bagian Wilayah Perencanaan Ibu Kota Negara Timur, Kalimantan Timur - Natasya Valentina Putri Tommy; Elin Diyah Syafitri; Rizky Arif Nugroho; Dwinsani Pratiwi Astha (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2023)
According to Law Number 3 of 2022 concerning the State Capital, Sepaku District is designated as a tourism and entertainment center area, namely BWP 4 or BWP IKN Timur. Based on the results of field observations, it is known that BWP IKN East has natural tourism potential in the form of mangrove forests, waterfalls, bamboo forests and caves. The natural beauty and beautiful villages can support the development of tourism. In its development, a tourism object must have six tourism criteria. Therefore it is necessary to analyze the tourism potential based on the six tourism criteria to support tourism development in BWP IKN Timur. As for the research method, the data used are primary data from field observations and documentation, and this research is qualitative in nature, and the analysis used is classification analysis through a scoring process. After conducting data analysis, it was found that BWP IKN East has tourism potential in the form of potential attractions, accessibility, amenities, ancillary, activities, and available packages.